Recent progress on mixed transition metal nanomaterials based on metal–organic frameworks for energy-related applications. Issue 18 (27th April 2022) - He, Yangzhuo; Yin, Zhuo; Wang, Ziwei; Wang, Han; Xiong, Weiping; Song, Biao; Qin, Hong; Xu, Piao; Zeng, Guangming
Abstract : Versatile types of MOF-derived mixed transition metal nanomaterials are summarized in terms of synthetic routes. The applications of those materials in energy storage and conversion, including LIBs, SCs, ORR, OER and HER are discussed. Abstract : MOF-derived mixed transition metal nanomaterials with tunable structure, high surface area, and adjustable pore size are attracting a great amount of research interest in many fields. This review focuses on the recent progress in the fabrication and utilization of MOF-derived mixed transition metal nanomaterials for energy-related fields. A variety of mixed transition metal nanomaterials, including mixed transition metal oxides/chalcogenides/phosphides/carbides/hydroxides, single-atom catalysts (SACs) with dual metal sites, alloys and their hybrids are systematically discussed related to the synthetic routes. Afterwards, the applications of these materials in energy storage and conversion, including lithium-ion batteries (LIBs), supercapacitors, hydrogen evolution reaction (HER), oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) are summarized. Finally, several challenges for the future development of MOF-derived mixed transition metal nanomaterials are proposed.